Association of timing of initial breastfeeding and neonatal outcome in very preterm infants: a multicentre cohort study in China - Rong Zhang; Chao Chen; Ling Yang; Hua Zhang; Ying Wu; Juan Chen; Hong Jiang; Yan Gao; Li Ma; Wei Zhou; Jie Yang; Shoo K Lee; et al. (BMJ Paediatrics Open, 2025)
Objective To evaluate the association between the timing of initial breastfeeding and the risk of necrotising enterocolitis (NEC) and other neonatal outcomes in very preterm infants (VPIs, <32 weeks’ gestation).Design Multicentre observational cohort study.Setting Data were collected from 102 tertiary neonatal intensive care units (NICUs) in China between 2019 and 2023 through the Chinese Neonatal Network.Patients A total of 12 679 VPIs admitted to NICUs within 24 hours of birth and initially breastfed within 7 days were included.Interventions Infants were categorised into four groups based on initial breastfeeding timing: within 24 hours (n=2242), 24–48 hours (n=3657), 48–72 hours (n=1870) and after 72 hours (n=4910, reference group).Main outcome measures The primary outcome was NEC (stage ≥2). Secondary outcomes included mortality, bronchopulmonary dysplasia, severe neurological injury, severe retinopathy of prematurity, late-onset sepsis, NICU length of stay and intravenous nutrition duration.Results Early breastfeeding initiation (<24 hours) was associated with a higher incidence of NEC (7.5% vs 4.3%, OR 1.92, 95% CI 1.21 to 3.06). No significant NEC risk increase was observed for feeding initiation after 24 hours. Early breastfeeding was linked to a shorter duration of intravenous nutrition (median 15 days (IQR 10–27) vs 22 days (IQR 14–33), mean difference −3.93 days, 95% CI −6.57 to −1.3). Subgroup analysis revealed increased NEC risk in neonates delivered via caesarean section, those receiving blood transfusions and those born <28 weeks’ gestation.Conclusions While early breastfeeding initiation (<24 hours) reduces intravenous nutrition duration, it may elevate NEC risk in specific high-risk subgroups. Feeding strategies should be individualised based on gestational age, delivery mode and transfusion status. Further randomised trials are needed to optimise early feeding protocols for VPIs.